PENTINGNYA MENANAMKAN NILAI-NILAI AKHLAK PADA ANAK USIA DINI - Widia Nurjanah; Rini Wahyuning Putri; Heni Yuliawati (Institut Madani Nusantara, 2022)
Teachers and parents have duties and responsibilities for the good and bad of children's Islamic religious education, this will have a positive or negative impact on the development of the younger generation in the future, this is where teachers are required to carry out their obligations by providing education and helping solve problems in children so that they do not experiencing difficulties in life. The objectives of this study are: 1) To find out the efforts made by teachers in the process of instilling moral values ??in early childhood at PAUD Tunas Harapan II Cisaat. 2) To find out the moral materials taught at PAUD Tunas Harapan II Cisaat. 3) To find out the method used in Tunas Harapan II Cisaat -Ikhlas Madium Rengas, Central Lampung. This type of research is field research. The nature of the research is descriptive qualitative. This study uses data collection techniques with interviews, observation and documentation. The data analysis technique used in this study uses data reduction (data reduction), data presentation (data display), and conclusions (conclusion drawing/verification). The results of data analysis showed that: 1) PAUD Tunas Harapan II Cisaat teacher in introducing and teaching the essence of religious teachings to children so that they can know and understand them and familiarize themselves with carrying out these religious teachings. The application of inculcating moral values ??in the PAUD is carried out in accordance with special education for early childhood children by taking into account the principles of early childhood development. 2) Moral materials applied in learning to early childhood at PAUD Tunas Harapan II Cisaat include human morals with Allah SWT, human morals with oneself, human morals with fellow humans and human morals with other creatures and their natural environment. 3) The method used in instilling moral values ??to early childhood teachers of PAUD Tunas Harapan II Cisaat uses the field trip method, the conversation method, the demonstration method, the storytelling method, the singing method and the assignment method.